Preparation method of Cu2S-CdS heterojunction nanosheet

By using CUSCN as the source of CU and S, combined with oily and TOP additives, ion exchange reactions are performed at room temperature, and CU2S-CDS heterogeneous nano-nanometers are prepared to solve the high energy consumption and toxic S source in existing technologies. The problem realizes high -efficiency, non -toxic nanoskin preparation and good electrical catalytic performance.

CN119332283AActive Publication Date: 2025-01-21NINGXIA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411220793.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-21
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

In the existing Cu2S-CdS nanosheet preparation methods, high energy consumption, strict temperature requirements, and toxic S sources, such as tert-dodecanthiol or dodecanthiol, are often used.

Method used

CUSCN is used as the source of CU and S, through vacuum heating and air-off treatment, combined with oilymine and TOP additives, ion exchange reactions are performed at room temperature to prepare CU2S-CDS heterogeneous nano-nanoplasty.

Benefits of technology

The CU2S-CDS nanometer preparation with low energy consumption and non-toxic S source has a high output, controllable size, intact, and good electrocatalytic CO2 reduction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332283A_ABST
    Figure CN119332283A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu2S-CdS heterojunction nanosheet preparation method, which specifically comprises: (1) carrying out vacuum heating on CuSCN and oleylamine, introducing saturated Ar, carrying out a heating reaction, cooling to a room temperature, adding toluene and methanol, centrifuging, washing, and drying to obtain a Cu2S hexagonal nanosheet; and (2) mixing a Cd (NO3) 24H2O methanol solution, tetrahydrofuran, TOP and a Cu2S hexagonal nanosheet toluene solution, degassing, reacting in an inert gas atmosphere, centrifuging, washing, performing ultrasonic treatment, centrifuging, washing, dispersing, centrifuging and drying to obtain the Cu2S hexagonal nanosheet. According to the preparation method, a toxic S source is not used, CuSCN is adopted as the S source and the Cu source at the same time to prepare a Cu2S parent, the Cu2S parent is applied to cation exchange of Cu2S reduction through electro-catalysis of CO2, and the hexagonal nanosheet which is intact in appearance and uniform and stable in size is prepared in a room-temperature stirring mode. The method is simple, low in cost, high in yield, small in loss and easy to prepare.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic reduction, and more particularly to a method for preparing Cu2S-CdS heterojunction nanosheets. Background Art

[0002] Nanostructures (NHs) consist of two or more components fused into a single nanoparticle (NP). There is growing interest in fabricating these structures, which are expected to play a greater role in important applications such as chemical catalysis and solar energy. Currently, existing synthetic methods are top-down, surface-grown, templated, or nanoreactor technologies, which often require specialized equipment and can only produce microgram quantities of NPs.

[0003] Cation exchange (CE) is a versatile and effective method for preparing novel colloidal nanostructures (NHs) and is widely used. When creating heterojunctions, appropriate method design is essential, as it involves dealing with multiple elements and multiple materials with well-defined interfaces. Ion exchange has been found to be highly effective in this context. It can further enhance catalytic performance by improving the catalyst surface environment and providing catalytic sites.

[0004] The conditions required for nanocrystal cation exchange to occur are mild, as the reaction occurs within seconds to minutes at temperatures ranging from below room temperature to several hundred degrees Celsius, far below the temperatures typically required to produce crystalline nanoparticles or bulk powders. Consequently, the anionic sublattice structure does not rearrange as the cations diffuse, resulting in products that retain key features of the precursor crystal structure. Because the anions are much larger than the cations, the anionic sublattice remains intact, effectively ensuring morphological continuity. In some cases, this sublattice retention can lead to the formation of crystal structures that are not thermodynamically preferred phases because they are kinetically trapped during the cation exchange process.

[0005] Existing cation exchange methods for preparing Cu2S-CdS nanosheets mostly use double-row tubes and high-temperature thermal reduction, which has high energy consumption and temperature requirements. In addition, most current Cu2S synthesis methods use thiols, including tert-dodecyl mercaptan or dodecanethiol, which are toxic S sources.

[0006] Therefore, how to develop a new preparation method for Cu2S-CdS heterojunction nanosheets is an urgent problem that technicians in this field need to solve. Summary of the Invention

[0007] In view of this, the object of the present invention is to provide a method for preparing Cu2S-CdS heterojunction nanosheets, so as to prepare size-controllable nanocatalysts using a simple method.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing Cu2S-CdS heterojunction nanosheets specifically comprises the following steps:

[0010] (1) CuSCN (cuprous thiocyanate) and oleylamine (cis-oleyl primary amine) were heated in a vacuum, saturated Ar was introduced, and the mixture was heated for reaction. The mixture was cooled to room temperature, toluene and methanol were added, and the mixture was centrifuged, washed, and dried to obtain Cu2S hexagonal nanosheets.

[0011] (2) Cd(NO3)24H2O (cadmium nitrate tetrahydrate) methanol solution, tetrahydrofuran, TOP (trioctylphosphine) and Cu2S hexagonal nanosheet toluene solution are mixed, degassed, reacted in an inert gas atmosphere, centrifuged, washed, sonicated, centrifuged, washed, dispersed, centrifuged, and dried to obtain Cu2S-CdS heterojunction nanosheets.

[0012] Furthermore, in the above step (1), the mass concentration of CuSCN is 95%-99%, preferably 99%; the mass concentration of oleylamine is 98%-99.99%, preferably 98%; and the usage ratio of CuSCN, oleylamine, toluene and methanol is 2.5mmol:15.20mmol:15mL:25mL.

[0013] A further beneficial effect of the above is that CuSCN can serve as a Cu source and provide S, and is non-toxic, replacing thiols that are toxic and have a pungent odor.

[0014] Oleylamine: used as a complexing agent and solvent, it can form a metal-oleylamine complex with CuSCN, and then further exchange the metal to form a ligand.

[0015] Toluene: used as an organic solvent, has good solubility, is used to dissolve Cu2S, and has good solubility.

[0016] Methanol: used as an organic solvent, it can quickly dissolve Cd(NO3)24H2O and has good dispersion, which is conducive to better dissolution.

[0017] Furthermore, in the above step (1), the vacuum heating temperature is 95-105°C, preferably 100°C, and the time is 5-15 min, preferably 10 min; the heating reaction temperature is 220-250°C, preferably 240°C, and the time is 25-35 min, preferably 30 min; the centrifugal speed is 4000-10000 rpm, preferably 4000 rpm, and the time is 2-10 min, preferably 5 min.

[0018] Furthermore, in the above step (1), the washing reagent is an ethanol / toluene mixture; the usage ratio of ethanol to toluene is (9-11) mL:(4-6) mL, preferably 10 mL:5 mL.

[0019] Furthermore, in the above step (1), the drying temperature is 60-75°C, preferably 70°C, and the drying time is 3-6h, preferably 3h;

[0020] Furthermore, in the above step (2), the concentration of the Cd(NO3)24H2O methanol solution is 0.1 mol / L; the concentration of the Cu2S hexagonal nanosheet toluene solution is 0.0786 mol / L (2 mL of toluene is added to 25 mg of Cu2S hexagonal nanosheets); the dosage ratio of the Cd(NO3)24H2O methanol solution, tetrahydrofuran, TOP and Cu2S hexagonal nanosheet toluene solution is (0.8-1.2) mL:(0.8-1.2) mL:(0.5-1) mL:(1.5-2.5) mL, preferably 1 mL:1 mL:0.5 mL:2 mL.

[0021] The further beneficial effect of the above is that Cd(NO3)24H2O is used to provide a Cd source. According to the theory of soft and hard acid and base, soft acid Cu + , extracted and replaced by hard acids, such as metal chalcogenides Cd using TOP 2+ As a soft base. TOP as an extractant, the soft acid Cu + Extracted, Cd 2+ Can form complexes with oleylamine; TOP is also a reducing agent. These compounds are able to bind metal ions by donating the P lone pair of electrons and forming a monodentate terminal metal-PR3 group (σ bonding). Unlike amine ligands that can only form σ bonds, phosphines can also be good π acceptors. Therefore, they can coordinate metal cations through π bonds, the extent of which depends on the nature of the R group. For these reasons, phosphines can be very high-field ligands and can form strong metal-ligand (ML) bonds. Oleylamine (OA) promotes the conversion of Cd to Cd by forming a stable Cd-OA complex. 2+ Extraction of ions.

[0022] Furthermore, in the above step (2), the reaction time is 22-24 hours, preferably 23 hours.

[0023] Furthermore, in the above step (2), the washing reagent is toluene, and the amount used is 1-2 mL, preferably mL.

[0024] Furthermore, in the above step (2), the dispersing reagent is toluene, and the amount used is 0.5-1 mL, preferably 1 mL.

[0025] Furthermore, in the above step (2), the drying temperature is 60-75°C, preferably 70°C, and the drying time is 5-8h, preferably 6h.

[0026] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] Instead of using a toxic sulfur source, the present invention uses CuSCN as both a sulfur and copper source to prepare a Cu2S matrix. This matrix is ​​then applied to the cation exchange electrocatalytic reduction of Cu2S by CO2. Hexagonal nanosheets with well-defined morphology, uniform size, and stability are prepared by stirring at room temperature. The method is simple, low-cost, high-yield, low-waste, and easy to prepare. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the process for preparing Cu2S-CdS heterojunction nanosheets;

[0029] Figure 2 This is a scanning electron microscope image of Cu2S-CdS-2 heterojunction nanosheets;

[0030] Figure 3 is the LSV curve;

[0031] Figure 4 The diagrams are gaseous and liquid product distribution, CO and H2 Faraday efficiency, and current density.

[0032] Figure 5 For FE CO And it data, in situ XRD patterns, Cu Auger spectra, electron microscopy images and high-resolution characterization images. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0034] Example 1

[0035] Preparation method of Cu2S-CdS heterojunction nanosheets, such as Figure 1 As shown, the specific steps include:

[0036] (1) 2.5 mmol of 99% CuSCN and 15.20 mmol of 98% oleylamine were placed in a 100 mL three-necked flask, heated at 100 °C under vacuum for 10 min, introduced saturated Ar, and then placed in a hot oil bath preheated to 240 °C for 30 min. After cooling to room temperature, 15 mL of toluene and 25 mL of methanol were added, and the mixture was centrifuged at 4000 rpm for 5 min. The mixture was washed with a 10 mL ethanol / 5 mL toluene mixture and finally dried in a vacuum drying oven at 70 °C for 3 h to obtain Cu2S hexagonal nanosheets.

[0037] (2) 1 mL of 0.1 mol / L Cd(NO3)24H2O methanol solution, 1 mL of tetrahydrofuran, 0.5 mL of TOP and 2 mL of 0.0786 mol / L Cu2S hexagonal nanosheet toluene solution were mixed, degassed to prevent oxidation, reacted in an inert atmosphere of nitrogen and argon for 23 h, centrifuged, washed with 2 mL of toluene, sonicated, centrifuged to remove organic residues, washed twice with 2 mL of toluene to remove excess cationic salts, dispersed in 1 mL of toluene, centrifuged, and finally dried in a vacuum drying oven at 70°C for 6 h to obtain Cu2S-CdS heterojunction nanosheets.

[0038] Example 2

[0039] Preparation method of Cu2S-CdS heterojunction nanosheets, such as Figure 1 As shown, the specific steps include:

[0040] (1) 2.5 mmol of 95% CuSCN and 15.20 mmol of 98% oleylamine were placed in a 100 mL three-necked flask, heated at 95°C under vacuum for 5 min, introduced saturated Ar, and then placed in a hot oil bath preheated to 220°C for 25 min. The mixture was cooled to room temperature, and 15 mL of toluene and 25 mL of methanol were added. The mixture was centrifuged at 4000 rpm for 2 min, washed with a 9 mL ethanol / 6 mL toluene mixture, and finally dried in a vacuum drying oven at 60°C for 3 h to obtain Cu2S hexagonal nanosheets.

[0041] (2) 0.8 mL of 0.1 mol / L Cd(NO3)24H2O methanol solution, 0.8 mL of tetrahydrofuran, 0.5 mL of TOP and 1.5 mL of 0.0786 mol / L Cu2S hexagonal nanosheet toluene solution were mixed, degassed to prevent oxidation, reacted in an inert atmosphere of nitrogen and argon for 22 h, centrifuged, washed with 1 mL of toluene, sonicated, centrifuged to remove organic residues, washed twice with 1 mL of toluene to remove excess cationic salts, dispersed in 0.5 mL of toluene, centrifuged, and finally dried in a vacuum drying oven at 60°C for 5 h to obtain Cu2S-CdS heterojunction nanosheets.

[0042] Example 3

[0043] Preparation method of Cu2S-CdS heterojunction nanosheets, such as Figure 1 As shown, the specific steps include:

[0044] (1) 2.5 mmol of 99% CuSCN and 15.20 mmol of 99.99% oleylamine were placed in a 100 mL three-necked flask, heated at 105°C under vacuum for 15 min, introduced saturated Ar, and then placed in a hot oil bath preheated to 250°C for 35 min. The mixture was cooled to room temperature, and 15 mL of toluene and 25 mL of methanol were added. The mixture was centrifuged at 10,000 rpm for 10 min, washed with a 11 mL ethanol / 4 mL toluene mixture, and finally dried in a vacuum drying oven at 75°C for 6 h to obtain Cu2S hexagonal nanosheets.

[0045] (2) 1.2 mL of 0.1 mol / L Cd(NO3)24H2O methanol solution, 1.2 mL of tetrahydrofuran, 1 mL of TOP and 2.5 mL of 0.0786 mol / L Cu2S hexagonal nanosheet toluene solution were mixed, degassed to prevent oxidation, reacted in an inert atmosphere of nitrogen and argon for 24 h, centrifuged, washed with 2 mL of toluene, sonicated, centrifuged to remove organic residues, washed twice with 2 mL of toluene to remove excess cationic salts, dispersed in 1 mL of toluene, centrifuged, and finally dried in a vacuum drying oven at 75°C for 8 h to obtain Cu2S-CdS heterojunction nanosheets.

[0046] Performance Testing

[0047] Take Cu2S prepared in Example 1, Cu2S-CdS-1 prepared in Example 1, Cu2S-CdS-2 prepared in Example 2, Cu2S-CdS-3 prepared in Example 3 and a commercially available CdS, and conduct the following tests respectively.

[0048] 1. Scanning electron microscope image

[0049] The scanning electron microscope image of Cu2S-CdS-2 heterojunction nanosheets is shown in Figure 2. Figure 2 shown.

[0050] Depend on Figure 2 It can be seen that the Cu2S-CdS-2 is well-dispersed and uniformly sized ultrathin hexagonal nanosheets, which proves that the method of the present invention is stable and can prepare uniform and stable hexagonal nanosheets.

[0051] 2. LSV curve

[0052] Linear sweep voltammetry (LSV) was used to examine the electrochemical activity of the catalysts at a scan rate of 10 mV s -1 , the scanning range is 0V-1.2V vs.RHE.

[0053] The LSV curves of Cu2S, Cu2S-CdS-1, Cu2S-CdS-2, Cu2S-CdS-3 and CdS are as follows Figure 3 As shown in a, the LSV curves of Cu2S-CdS-2 in CO2 and N2 are as follows Figure 3 As shown in b.

[0054] Depend on Figure 3 As shown in Figure a, the current density of the Cu2S-CdS heterojunction nanosheets of the present invention is significantly increased compared to Cu2S and CdS. In addition, as the cation exchange proceeds and the CdS content increases, the activity shows a volcano-type trend, which is attributed to the influence of a moderate heterojunction. That is, by constructing a moderate heterojunction interface of Cu2S-CdS, the surface charge distribution of the material is significantly changed, thereby affecting the adsorption energy of the reaction intermediates. The moderate heterojunction promotes charge transfer between the active materials, showing good electrocatalytic CO2 activity.

[0055] Depend on Figure 3 As shown in Figure b, the current density of the Cu2S-CdS-2 heterojunction catalyst under CO2 atmosphere is significantly higher than that under N2 atmosphere, indicating that it has excellent CO2 reduction ability.

[0056] 3. Gaseous and liquid product distribution diagrams, CO and H2 Faraday efficiency diagrams, and current density diagrams

[0057] The gaseous and liquid product distribution diagrams of Cu2S, Cu2S-CdS-2 and CdS are shown in Figure 2. Figure 4 As shown in Figures ac, the CO Faraday efficiency diagram, H2 Faraday efficiency diagram and partial current density diagram of CO applied potential of Cu2S, Cu2S-CdS-1, Cu2S-CdS-2, Cu2S-CdS-3 and CdS are shown in Figures ac and ac, respectively. Figure 4 As shown in df.

[0058] Depend on Figure 4 It can be seen that compared with Cu2S and CdS, the CO2RR activity of the Cu2S-CdS heterojunction nanosheets of the present invention is significantly enhanced, and the HER is significantly suppressed overall.

[0059] 4. FE CO and it data, in-situ XRD patterns, Cu Auger spectra, electron microscopy images and high-resolution characterization images

[0060] FE of Cu2S-CdS-2 electrolyzed at -0.77 V vs. RHE for 45 h CO and it data such as Figure 5 As shown in a, the in-situ XRD pattern, Cu Auger spectrum, electron microscopy and high-resolution characterization of Cu2S-CdS-2 after electrolysis in CO2-saturated 0.5M KHCO3 solution are shown in Figure 2. Figure 5 As shown in be.

[0061] Depend on Figure 5 As shown in a, Cu2S-CdS-2 is about 10 mA cm in the H-type electrolytic cell. -2 The current density can be stably operated for at least 45 h. After consuming 45 h at -0.77 V vs. RHE, the CO content was measured, and its FEs remained essentially unchanged from 5 to 45 h (84% for 5 h and 80% for 45 h), indicating that Cu2S-CdS-2 has good stability and excellent electrochemical activity.

[0062] Depend on Figure 5 As can be seen from Figure 2, XRD was further used to verify the stability of the crystal structure of Cu2S-CdS-2 during the electrolysis process. The spectrum of Cu2S-CdS-2 showed that the 32.0° and 46.0° were attributed to the (200) and (220) crystal planes (PDF#02-1280), and the new 2θ diffraction peaks at 43.91° and 51.91° were attributed to the (110) and (112) crystal planes of CdS, respectively (PDF#02-0549). This confirmed that the Cu2S-CdS catalyst was successfully synthesized by cation exchange, and no phase transition occurred during the entire electrolysis process, which further demonstrated that the catalyst had good stability.

[0063] Depend on Figure 5 It can be seen from the figure that Cu2S-CdS-2 can still maintain a stable hexagonal nanosheet morphology after electrolysis.

[0064] The above description of the disclosed embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing Cu2S-CdS heterojunction nanosheets, characterized in that: The specific steps include: (1) heating CuSCN and oleylamine in vacuum, introducing saturated Ar, heating for reaction, cooling to room temperature, adding toluene and methanol, centrifuging, washing, and drying to obtain Cu2S hexagonal nanosheets; (2) Mixing Cd(NO3)24H2O methanol solution, tetrahydrofuran, TOP and Cu2S hexagonal nanosheet toluene solution, degassing, reacting in an inert gas atmosphere, centrifuging, washing, ultrasonicating, centrifuging, washing, dispersing, centrifuging and drying to obtain the Cu2S-CdS heterojunction nanosheets.

2. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (1), the mass concentration of CuSCN is 95%-99%; the mass concentration of oleylamine is 98%-99.99%; the usage ratio of CuSCN, oleylamine, toluene and methanol is 2.5mmol:15.20mmol:15mL:25mL.

3. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (1), the temperature of the vacuum heating is 95-105°C, and the time is 5-15 min; the temperature of the heating reaction is 220-250°C, and the time is 25-35 min; the speed of the centrifugation is 4000-10000 rpm, and the time is 2-10 min.

4. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (1), the washing reagent is an ethanol / toluene mixture; the usage ratio of the ethanol and toluene is (9-11) mL:(4-6) mL.

5. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (1), the drying temperature is 60-75° C. and the drying time is 3-6 hours.

6. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (2), the concentration of the Cd(NO3)24H2O methanol solution is 0.1 mol / L; the concentration of the Cu2S hexagonal nanosheet toluene solution is 0.0786 mol / L; the dosage ratio of the Cd(NO3)24H2O methanol solution, tetrahydrofuran, TOP and Cu2S hexagonal nanosheet toluene solution is (0.8-1.2) mL: (0.8-1.2) mL: (0.5-1) mL: (1.5-2.5) mL.

7. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (2), the reaction time is 22-24 hours.

8. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (2), the washing reagent is toluene, and the amount used is 1-2 mL.

9. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (2), the dispersing reagent is toluene, and the amount used is 0.5-1 mL.

10. The method for preparing a Cu2S-CdS heterojunction nanosheet according to claim 1, characterized in that: In step (2), the drying temperature is 60-75° C. and the drying time is 5-8 hours.

Citation Information

Patent Citations

  • Method for regulating and controlling cation exchange reaction rate of Cu2-xS nanosheet

    CN112573557A

  • Preparation method of flaky cadmium sulfide-cuprous sulfide nano heterostructure material

    CN112960687A

  • Preparation methods and application of copper-based MOF catalyst and carbon-coated copper-based MOF catalyst

    CN113913865A

  • Metal sulfide nanoparticles and preparation method therefor

    WO2016195244A1